Non-tuberculous mycobacterial pulmonary disease - Cowman, Steven; van Ingen, Jakko; Griffith, David E; Loebinger, Michael R (The European respiratory journal, 2019)
Nontuberculous mycobacterial pulmonary disease (NTM-PD) is a challenging infection which is becoming increasingly prevalent, particularly in the elderly, for reasons which are unknown. While underlying lung disease is a well-established risk factor for NTM-PD, it may also occur in apparently healthy individuals. No single common genetic or immunological defect has been identified in this group, and it is likely that multiple pathways contribute towards host susceptibility to NTM-PD which further interact with environmental and microbiological factors leading to the development of disease.The diagnosis of NTM-PD relies on the integration of clinical, radiological and microbiological results. The clinical course of NTM-PD is heterogeneous, with some patients remaining stable without the need for treatment and others developing refractory disease associated with considerable mortality and morbidity. Treatment regimens are based on the identity of the isolated species, drug sensitivity testing (for some agents) and the severity of disease. Multiple antibiotics are typically required for prolonged periods of time and treatment is frequently poorly tolerated. Surgery may be beneficial in selected cases. In some circumstances cure may not be attainable and there is a pressing need for better regimens to treat refractory and drug-resistant NTM-PD.This review summarises current knowledge on the epidemiology, aetiology and diagnosis of NTM-PD and discusses the treatment of two of the most clinically significant species, the and complexes, with a focus on refractory disease and novel therapies.